Integrasi Nilai-Nilai Moderasi Beragama dalam Kurikulum Mendasar - Imetrimawati Imetrimawati; Efata Emanuel Gulo; Lifertin Zebua; Wita Serlina Waruwu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Religious moderation represents one of the fundamental values in shaping a tolerant, inclusive, and civilized national character. Integrating the values of religious moderation into the basic education curriculum serves as a strategic effort to instill moderate religious attitudes from an early age. This article aims to analyze the concept, urgency, and implementation of integrating religious moderation values within Indonesia’s basic education curriculum. Using a qualitative-descriptive approach through literature review, this study finds that the implementation of religious moderation can be realized through strengthening the Pancasila student profile, promoting interfaith learning, and embedding the values of tolerance and justice across all subjects. The findings indicate that a curriculum incorporating religious moderation not only develops students’ cognitive competencies but also fosters a religious character that appreciates diversity. The study concludes that religious moderation in the curriculum can significantly improve students' cognitive development, while simultaneously cultivating a religious character that embodies the values of tolerance, justice, and social responsibility. Such integration is vital to ensuring a peaceful and prosperous future for the nation.